OLDER AND YOUNGER ADULTS' STRATEGIC CONTROL OF METACOGNITIVE MONITORING: THE ROLE OF CONSEQUENCES, TASK EXPERIENCE, AND PRIOR KNOWLEDGE. Issue 3 (27th May 2017) - McGillivray, Shannon; Castel, Alan D.
Abstract : Background/Study Context: Although explicit memory abilities decline during older adulthood, there is evidence that suggests that metacognitive capabilities are relatively well preserved. However, it is unclear what effect aging, consequences of forgetting, prior knowledge, and task experience have on the strategic control and use of one's metacognitive capabilities. Methods: In the current study, older and younger adults were presented with six unique lists of words (Experiment 1), related and unrelated word pairs (Experiment 2), or items within specific scenarios (e.g., items to bring on a picnic; Experiment 3). For each item, participants assigned it a point value (from 0 to 10) that was akin to "betting" on the likelihood the item would be remembered. If the item was recalled (free recall in Experiments 1 and 3, cued recall in Experiment 2), participants received the points they had assigned to it, but if the item was forgotten they lost those points. Participants were told to maximize their point score and were told their score at the end of each list. Results: Although younger adults remembered more words in Experiment 1, older and younger adults were equally able to remember items assigned higher values, and accuracy of predictions and point scores increased with task experience. In Experiments 2 and 3, when participants were able to rely on semantic knowledge, age-related differences in memory performance were eliminated. Conclusion: The results suggest that both younger and older adults achieve accurate metacognitive insight and are able to use this knowledge strategically in order to maximize goal-related memory outcomes and performance.